2019
DOI: 10.1177/1178221819878765
|View full text |Cite
|
Sign up to set email alerts
|

Financial Hardship, Motivation to Quit and Post-Quit Spending Plans among Low-Income Smokers Enrolled in a Smoking Cessation Trial

Abstract: Background: Tobacco spending may exacerbate financial hardship in low-income populations by using funds that could go toward essentials. This study examined post-quit spending plans among low-income smokers and whether financial hardship was positively associated with motivation to quit in the sample. Methods: We analyzed data from the baseline survey of a randomized controlled trial testing novel a smoking cessation intervention for low-income smokers in New York City ( N = 410). Linear regression was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Monthly pocket money had no significant effect on the level of motivation to quit smoking [16]. However, another study had shown that respondents who had lower incomes/pocket money had the motivation to quit smoking [17].…”
Section: Discussionmentioning
confidence: 93%
“…Monthly pocket money had no significant effect on the level of motivation to quit smoking [16]. However, another study had shown that respondents who had lower incomes/pocket money had the motivation to quit smoking [17].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, most international studies on correlations with motivation to stop focused solely on intentions to stop, which does not represent the concept of motivation comprehensively 3. When motivation to stop was investigated, it is still difficult to compare research results since most studies used different measures to assess motivation 4 6 15 16. The Motivation To Stop Scale (MTSS) is a single-item measure for motivation to stop based on the PRIME theory, which maps motivation fully combining its different aspects (intention, belief, desire) 3 17 18.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Greater financial strain is also associated with lower motivation to quit and increased relapse. 12 , 13 Dealing with social needs such as overdue rent, unpaid bills or food insecurity likely supersede interests in quitting smoking. 14 , 15 This is not simply prioritization, but also because having unmet social needs can diminish one’s cognitive capacity to focus on other goals, leading to shorter term thinking and decision-making that focuses on immediate needs.…”
Section: Introductionmentioning
confidence: 99%